Non-invasive prenatal paternity testing with STRs: A pilot study. (December 2015) - Gysi, M.; Arora, N.; Sulzer, A.; Voegeli, P.; Kratzer, A.
Abstract: Non-invasive prenatal paternity testing using foetal cell-free DNA (cfDNA) in the mother's blood eliminates the risks of miscarriage associated with invasive methods such as chorionic villus sampling and amniocentesis. However, the low abundance of cfDNA as well as the large excess of maternal cfDNA makes foetal DNA typing very challenging. As illustrated by our case study, SNP typing at 317, 000 positions using cfDNA in the mother's blood was shown to successfully identify the father. However, for forensic routine work, STR analysis would be preferable over SNP analysis, as for STR markers the frequencies and population data are available and the statistics are well established. We therefore initiated a pilot study to set up a next-generation sequencing (NGS) assay using an early access version of the Ion AmpliSeq HID STR 25-plex on the Ion PGM™. We successfully confirmed paternity from blood samples from two pregnant women with 10 and 16 weeks of gestation (GW). Drop-outs were not observed but further testing is necessary for a full evaluation. Overall, our data suggest that paternity testing with STRs and NGS is a promising approach for non-invasive prenatal paternity testing.